Integration of research and teaching practices and the training of reflective professionals - Jacques Therrien; Silvia Maria Nóbrega Therrien (Universidade Federal de Santa Maria, 2013)
This study approaches critical reflexivity as a mediating element of the integration between research and teaching practices in the training of the education professional. Based on the parameter of research as an educational principle associated to the presupposition that involvement in research activities encourages the development of rationalities that support reflective practices, which lead the most significant and independent learning processes, this essay aims at, on the one hand, identifying "macro" theoretic schemes that may support the analysis of different knowledge types and therefore, the rationalities that affect theory-practice dynamics in education initiatives and on the other hand, finding "micro" theoretical-practical schemes for reflective training related to the practice in learning contexts. The study analyzes proposals made by reference authors, as well as educational practices that support enunciated presuppositions.